x+3 DX XDX
x+3 DX XDX
x+3 DX XDX
∫ x dx + ∫ 3 dx
1 +1
x
+3x +c
1+ 1
x2
+3x+c
2
∫ ( 2 x−3 x 2 ) dx
∫ 2 x dx- ∫ 3 x 2 dx
2 x 1+1 3 x 2+ 1
- +c
1+1 2+1
2 3
2x 3x
- +c
2 3
2 3
x -x + c
∫ ( x 3 +2 ) dx
∫ x 3 dx +∫ 2 dx
3 +1
x
+ 2x + c
3+1
x4
+ 2x + c
4
∫ ( x +2 x+1 ) dx
3
2
∫ ( x ) dx +∫ 2 x dx +∫ 1 dx
3
2
3
+1
x2 x
1 +1
3 +2 +x +c
+1 1+ 1
2
5
2
x 2
5 + x +x +c
2
5
2 x 2 + x 2+x +c
5
∫ √3 x 2 dx
2
∫ x 3 dx
2
+1
3
x
2 +c
+1
3
5
3 x 3 +c
5
1
∫ x 3 dx
∫ x −3 dx
X =u3 +2
dx
=¿3u2
du
dx 2
=u du
3
2 3
f ( x )=
9
√x
3
2
f ( x )= x 2
9
d y 2 3 32 −1
= x
dx 9 2
dy 2 3 12
= x
dx 9 2
1
dy 1 2
= x
dx 3
dy 1
= √x
dx 3
u
2
√ u 3+ 2
∫ x 2−31 x+ 2 dx
3